Feed or fight: A behavioral shift in blind cavefish - Rétaux, Sylvie (Landes Bioscience, 2013)
Within the species Astyanax mexicanus, there are several inter-fertile populations of river-dwelling sighted fish and cave-dwelling blind fish which have evolved morphological and behavioral adaptations. We have recently reported a developmental and neurophysiological basis for the loss of aggressive behavior in the blind cavefish morph of Astyanax. Using an appropriate behavioral assay, we have shown that surface Astyanax show intense dominance-related aggressiveness. The expression of this behavior is inversely correlated with the serotonin (5HT) levels in their hindbrain raphe nucleus. Moreover this behavior is not solely visually-evoked and has a genetic component. Conversely in cavefish, there is no raphe-driven dominance aggressiveness. Instead, the embryonic Sonic Hedgehog–dependent modification of the size of a serotonergic neuronal group localized in their hypothalamus causes a shift in their behavioral pattern: instead of fighting, they search for food. Here we further discuss the origin and nature of this behavioral shift.